Immunological parameters in the aged and in Alzheimer's disease. - Macdonald, S M (1982)
Peripheral blood from patients with Alzheimer's disease, elderly normal subjects and young (normal subjects) was examined with respect to leucocyte phenotypes and proliferative responses to lectins. Whole blood cell analysis showed that the neutrophil count was similar in all three groups. However, the lymphocyte count was depressed in the Alzheimer group. The monocyte count was reduced in the healthy aged and further reduced in the Alzheimer group. Analysis of peripheral blood mononuclear cells showed no change in the proportion of E+ cells, total T determined with the monoclonal antibody UCHT1 (similar to OKT3) and the T cell subsets: active E and T dot (discrete esterase staining). However, the proportion of T cells bearing the antigen detected by UCHT3 monoclonal antibody (similar to Leu 1 and OKT1) was reduced in the healthy aged and further reduced in the Alzheimer group. Proliferative responses to PHA, Con A, PA, and PWM were similarly depressed in both the aged and Alzheimer groups.